Evaluating the Antioxidant Capacity of Rheum Ribes via Cupric Reducing Antioxidant Capacity, Ferric Reducing Antioxidant Power and 2,2-Diphenyl-1- picrylhydrazyl Methods - Esen Sezen Karaoğlan; Onur Senol; Semih Özli (Pharmata)
Objective: It was aimed at determining the antioxidant capacity of the above-ground parts of the Rheum ribes species, known as “Iskın,” which grows in the high parts of Erzurum province, using different methods.Methods: Methanol extracts have been prepared to determine the antioxidant capacity of the Rheum ribes plant. The samples were then analyzed with cupric reducing antioxidant capacity, ferric reducing antioxidant power, 2,2-diphenyl-1-picrylhydrazyl radicals. As a reference sample, gallic acid compounds were reacted with the same radicals in different concentrations. The reference sample was determined for equivalent antioxidant capacity methanol extracts.Results: Gallic acid was used as a reference standard along with the in vitro capacity measurements. The working range was determined where the absorbance graph was linear, and the calibration curves were plotted. The “Iskın” sample was then measured using the same workflow, with 6 consecutive samples. The antioxidant capacity of rhubarb samples was calculated in terms of gallic acid equivalent µg/mL.Conclusion: In the study, the antioxidant capacity of rhubarb plant was determined using different methods. The response of the rhubarb plant against triphenyltetrazolinechloride, neocuproin, diphenyl picryl hydrazine radicals was determined by spectrophotometric measurements, and the findings were compared with the reference gallic acid sample. According to the results, it was determined that this endemic plant exhibited a very high antioxidant capacity. For this reason, it is thought that crop planting for this wild plant may lead to a remarkable contribution to the industry of the local region and may be used in the cosmetic and drug industries.